Studi Kepuasan Pelayanan Kesehatan Masyarakat di Puskesmas Sungai Kapih Kota Samarinda - Astuti, Ashri Budi; Adrianto, Ratno; Baharudin, Irfansyah; Kartikasari , Dina (Jurnal Kesehatan Komunitas, 2025)
A long with technological advancements and societal demands for services, public service providers are required to meet the expectations of the community in delivering services. One of the efforts that must be made in improving public services is conducting community satisfaction surveys. The purpose of this research is to provide an overview of public satisfaction with the services received. The survey is conducted periodically using a descriptive method approach, where the measurement employs the Likert Scale. The respondents in this study were determined based on the Krejcie and Morgan table, consisting of 70 men and 105 women. This survey was conducted at the Sungai Kapih Health Center in Samarinda City from July to October 2024. Data collection was conducted using questionnaires and interviews with respondents who came to the health center. The results of this survey indicate that the complaint and facility elements have a lower satisfaction index compared to other elements. This is caused by the Sungai Kapih Health Center, which is currently providing services at a temporary location in a rented shop,where one of the components that can influence customer satisfaction is direct evidence or physical evidence (tangibles), namely facilities and infrastructure that can be felt directly or physically by customers. It is hoped that after the renovation process is complete, services can run smoothly, with better and more adequate facilities and infrastructure so that patient expectations and comfort are met. Patient satisfaction is a benchmark in the performance of public services, so it is necessary to immediately meet the expectations of the community regarding the provision of facilities and infrastructure in services at the health center.